2017
DOI: 10.1161/jaha.117.005522
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Perconditioning to Reduce Reperfusion Injury During Acute ST‐Segment–Elevation Myocardial Infarction: A Systematic Review and Meta‐Analysis

Abstract: BackgroundRemote ischemic conditioning (RIC) is a noninvasive therapeutic strategy that uses brief cycles of blood pressure cuff inflation and deflation to protect the myocardium against ischemia–reperfusion injury. The objective of this systematic review was to determine the impact of RIC on myocardial salvage index, infarct size, and major adverse cardiovascular events when initiated before catheterization.Methods and ResultsElectronic searches of Medline, Embase, and Cochrane Central Register of Controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…These combined effects are expected to help promote myocardial recovery. Other possible approaches that have been evaluated to reduce reperfusion injury following PCI in patients with STEMI have included ischemic conditioning [48,49] and adenosine [50,51]: the results of these studies varied in terms of myocardial protection and survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…These combined effects are expected to help promote myocardial recovery. Other possible approaches that have been evaluated to reduce reperfusion injury following PCI in patients with STEMI have included ischemic conditioning [48,49] and adenosine [50,51]: the results of these studies varied in terms of myocardial protection and survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…After the advent of the experimental evidences of positive effects of IPC in I/R injury, several clinical studies started to show conflicting results about the real benefits of this procedure in medical practice. Recently, studies with a high level of evidence, as clinical trials, systematic reviews, and meta-analyses have demonstrated beneficial effects of direct or remote IPC in clinical situations involving myocardial 15,16 , renal 17 , and neuronal ischemia 18 . However, it is known that different tissue and organ sensitivities to ischemia are diverse so that such benefits cannot be generalized.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The recovery of myocardial tissue is the main goal of therapy in emergency settings and can be achieved by urgent revascularization. [14][15][16] In order to be effective, reperfusion of an occluded coronary artery should be achieved in the first 12 hours after the onset of chest pain. 17 While many precious hours are lost by the patients who do not present in time to the specialized services, sustained organizational efforts have been made in order to shorten the time from presentation to revascularization.…”
Section: Stemi Networkmentioning
confidence: 99%